2010
DOI: 10.1002/prep.200800087
|View full text |Cite
|
Sign up to set email alerts
|

Micro Videographic Analysis of the Melt Layer of Self‐Deflagrating HMX and RDX

Abstract: Micro videographic analysis of the thin molten layer on the surface of HMX (Octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine) and RDX (Hexahydro-1,3,5-trinitro-1,3,5-triazine) during self deflagration were performed. This was done to gain a better understanding of the physical structure present in this 100 -300 mm layer and give a visual picture for the development of computational models. During steady-state combustion, RDX had a consistent melt layer with vigorous bubble formation. There was a continuous liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Deflagrating explosives burn faster and more violently than non-explosive combustible materials, which require an external supply of oxygen to sustain the burning [15]. Laser-induced deflagrations have been investigated using laser pulses hundreds of microseconds or longer on HMX [16][17][18], TATB [16,17], RDX [18][19][20], and rocket propellants [21]. McGrane and Moore also investigated the effect of CW laser wavelength on the reaction of various explosives [22].…”
Section: Introductionmentioning
confidence: 99%
“…Deflagrating explosives burn faster and more violently than non-explosive combustible materials, which require an external supply of oxygen to sustain the burning [15]. Laser-induced deflagrations have been investigated using laser pulses hundreds of microseconds or longer on HMX [16][17][18], TATB [16,17], RDX [18][19][20], and rocket propellants [21]. McGrane and Moore also investigated the effect of CW laser wavelength on the reaction of various explosives [22].…”
Section: Introductionmentioning
confidence: 99%
“…At the higher pressures, minimal expansion occurs leading to a more homogeneous structure. If this theory is true, then this data may be indirect evidence of a foam or froth layer similar to RDX and HMX [3]. Further data is needed to determine if the melt layer is formed by CL-20 and/or HTPB.…”
Section: Full Papermentioning
confidence: 97%
“…The result is a carbonaceous ash residue remains following decomposition of CL-20 [2]. A melt layer is present in both RDX and HMX flames and its structure is believed to influence the temperature and pressure dependence of the burning rate [3]. No experimental evidence has been reported that definitively shows a melt layer for CL-20 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have shown that many solid propellants exhibit a thin liquid layer with gaseous bubbles ("foam" layer), typically a few micrometers thick for AP-based propellants [14]. For HMX/RDX propellants at ambient pressure, the melt layer can be around 200 micrometers thick [43], while the gas flame thickness is around 5 millimeters. At higher pressure, both thicknesses decrease [44].…”
Section: General Modellingmentioning
confidence: 99%